A Cadaver Study Revisiting the Original Methodology of Lauge-Hansen and a Commentary on Modern Usage. (1st April 2015) - Kwon, John Y.; Gitajn, Ida Leah; Walton, Phillip; Miller, Timothy J.; Appleton, Paul; Rodriguez, Edward K.
Abstract : Background: The study by Lauge-Hansen published in the Archives of Surgery in 1950 still stands as the seminal work for our understanding of the pathomechanics of ankle fractures. The purpose of the present study was to recreate Lauge-Hansen's experiments for the supination-external rotation (SER) fracture mechanism and to determine whether the predicted sequence of osseous and soft-tissue injury is reproducible on the basis of his originally described methodology. Methods: Ten fresh-frozen cadaver specimens amputated above the knee were utilized. The foot was axially loaded in a position of neutral dorsiflexion and supination. External rotation was applied manually in accordance with Lauge-Hansen's description until osseous and/or soft-tissue injury occurred. Fluoroscopic images were made and anatomic dissection was performed. Results: Although several specimens exhibited findings consistent with certain stages of the SER injury pattern, no specimen demonstrated the complete sequence of predicted osseous and soft-tissue injury. Conclusions: Loading cadaver specimens with an SER mechanism utilizing a methodology similar to that in the original experiments by Lauge-Hansen does not reliably produce the sequence of osseous and soft-tissue injury predicted by Lauge-Hansen.